Ação antitrombótica, antiagregante, antioxidante e moduladora da função vascular em ratos suplementados com o óleo da amêndoa do Baru (Dipteryx alata Vog.) - Luis, Cristiane Cosmo Silva (2018)
Thrombosis is a Cardiovascular Disease (CVD) that increases the risk of death when it is related to the pathological mechanisms of Ischemic Heart Disease and Ischemic Stroke. The development of CVDs is inversely related to the consumption of foods rich in vitamin E nutrients (Vit. E), omegas 3 and 9. The objective of this study was to evaluate the effect of supplementation of the almond oil of Dipteryx alata Vog. (D. alata Vog.) On induced thrombosis and platelet aggregation in rats. Therefore, tocopherols were quantified in the oil and toxicity was assessed on the Central Nervous System (CNS) and Autonomous System (ANS). The oral treatment lasted 10 days, the Control group received 1 mL of 0.9 % NaCl, the two groups supplemented with the oil of D. alata Vog. received doses of 7.2 mg/kg/day and 14.4 mg/kg/day each and Vit. E received 0.42 mg/kg/day of a pharmaceutical formulation of Vit. E diluted in 0.2 mL of mineral oil. On the 11th day after the 10-day supplementation period, the experimental protocol with induction of thrombosis in the carotid artery with FeCl3 and monitoring of blood flow with subsequent dissection of the carotid artery to remove the thrombus was started; in plasma were analyzed platelet aggregation, superoxide anion production (O2•-) and tocopherols quantification; the thoracic aorta artery was dissected for vascular reactivity analysis. According to the results obtained the tocopherols content found in the oil was 2.89 % and the toxicity evaluation showed that the doses tested of 300 and 2000 mg/kg of the oil did not caused behavioral alterations nor neither deaths of the animals. The oil of D. alata Vog. in the dose 14.4 mg/kg had an antithrombotic effect promoting an increase in the occlusion time in this group of 138.6 % and a reduction in the weights of the wet and dry thrombi of 24 h in 62.9 and 61.8 %, respectively, compared to control. The dose D. alata Vog. 14.4 mg/kg also caused a 31 % decrease in ADP-induced platelet aggregation in relation to Control. The measurement of the DHE fluorescence showed a decrease in the O2•- production of 43 % in the D. alata Vog.7.2 mg/kg group and 32.8 % in the Vit. E. The emission of the fluorescence of the DHE in the aggregate platelet was 75.1 % in D. alata Vog. 7.2 mg/kg, 76.6 %, in D. alata Vog. 14.4 mg/kg and 79.4 % in Vit.E, all emission measurements in relation to controls. The reactivity study showed that the oil of D. alata Vog. at doses 7.2 mg/kg, 14.4 mg/kg and Vit. E 0.42 mg/kg reduced the Phe contraction Emax in the vessel at 36.4; 57.7 and 42 %, respectively, compared to Control. Already in the rings without endothelium the oil of D. alata Vog. at 7.2 mg/kg decreased by 33.8 % and at the dose 14.4 mg/kg decreased the Emax of contraction of Phe in the vessel by 35.2 % compared to Control, but this effect was more pronounced in the presence of endothelium. In the group supplemented with the oil of D. alata Vog. dose 14.4 mg/kg, there was an increase in pD2 of the vasorelaxant agents, ACh in 14.6 % compared to Vit. E 0.42 mg/kg and NPS at 17.6; 15.5 and 13.8 % compared to Control, D. alata Vog. 7.2 mg/kg and Vit. E and 0.42 mg/kg, respectively. Therefore, the findings indicate that the oil is non-toxic at the doses tested, prevents thrombosis, reduces platelet aggregation and produces O2 • - and modulates vascular function, showing superior effect to Vit.E. Thus, its use may be a possible strategy for the prevention of CVDs.